Climate-smart aquaculture practices for smallholder fish farmers in Zambia: Integrated fish-livestock training workshop report - Lundeba, Mary; Mudege, Netsayi; Mwema, Catherine; Siamudaala, Victor (WorldFish, 2022)
Training on climate-smart aquaculture (CSA) practices for smallholder fish farmers targeted small- and medium-sized entrepreneurs (SMEs) in Zambia, as well as fisheries and livestock extension officers offering services to the farmers. The SMEs included recipients of accelerator grants from the Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project that were given for the aquaculture value chain and other SMEs offering aquaculture-related goods and services.